Rural area of the Brazilian Pantanal wetlands associated with the occurrence of anti-Leishmania spp. antibodies in dogs - Melo, Andréia Lima Tomé; Costa, Andréa Pereira da; Miyazaki, Selma Samiko; Stocco, Matias Bassinello; Semedo, Thiago Borges Fernandes; Pacheco, Thábata dos Anjos; Witter, Rute; Pacheco, Richard de Campos; Labruna, Marcelo Bahia; Marcili, Arlei; Aguiar, Daniel Moura de (Brazilian Journal of Veterinary Research and Animal Science, 2017)
An evaluation was made of the presence of anti-Leishmania infantum chagasi antibodies in domestic dogs from the urban and rural areas of Brazil’s Pantanal wetland region using serological techniques. A total of 429 dogs were sampled in three areas of the Pantanal biome, including the municipalities of Poconé, Santo Antônio de Leverger, and Barão de Melgaço, in the state of Mato Grosso, and in the municipality of Corumbá, in the state of Mato Grosso do Sul. The immunofluorescence assay (IFA) was used to detect antibodies (cut-off point 40) using Leishmania infantum chagasi antigen. Because of the possibility of cross-reactivity between species of the genus Leishmania, samples that were positive in the IFA against L. infantum chagasi were also tested by IFA in the same conditions, using L. amazonensis and L. braziliensis antigens. IFA-positive samples to L. infantum chagasi were also evaluated using Enzyme-Linked Immunosorbent Assay (ELISA). The results showed the presence of antibodies against L. infantum chagasi in 23 (5.36%; 95% CI: 3.50%-8.05%) dogs and at least one seroreactive dog was found in each of the municipalities evaluated in this study. Antibody titers ranged from 40 to 5,120, and all IFA positive samples were positive in the ELISA. Among the 23 positive dogs, nine were also were seroreactive for L. amazonensis and L. braziliensis antigens. The occurrence of anti- L. infantum chagasi antibodies in dogs was higher in rural areas (7.06%) than in urban areas (2.50%) (P < 0.05). Based on this study, we concluded that dogs from rural areas of the Pantanal wetlands were in contact with Leishmania species, which is relevant information given their importance to public health.